T Follicular Helper-Like Cells Are Involved in the Pathogenesis of Experimental Autoimmune Encephalomyelitis - Guo, Jun; Zhao, Cong; Wu, Fang; Tao, Liang; Zhang, Chunmei; Zhao, Daidi; Yang, Shuya; Jiang, Dongbo; Wang, Jing; Sun, Yuanjie; Li, Zhuyi; Li, Hongzeng; et al. (Frontiers in Immunology, 2018)
Multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE) have been proved to be T cell-mediated autoimmune diseases. Recent researches indicate that humoral immunity is also involved in the pathogenesis of these disorders. T follicular helper cells (Tfh) are critical for B cell differentiation and antibody production. However, the role of Tfh cells in MS and EAE remains unclear. Here, we found elevated frequencies of CD4+CXCR5+PD-1+ Tfh-like cells in both MS patients and EAE. In EAE mice, Tfh-like cells, together with B cells, were found in the ectopic lymphoid structures in spinal cords. Moreover, Tfh-like cells promoted the antibody production via IL-21/IL-21R and CD40L/CD40 interaction and the synergy effect of STAT3 and non-canonical NF-kB signaling pathway inside B cells. Moreover, adoptive transfer of Tfh-like cells could increase the severity and delay the remission of EAE. In conclusion, our data indicated that Tfh-like cells contribute to the pathogenesis of EAE.